Therapeutic options in osteoporosis - Dominguez, Ligia J.; Scalisi, Rosalinda; Barbagallo, Mario (Acta Biomedica Atenei Parmensis, 2010)
Osteoporosis is a major and global public health concern. This disorder is characterized by a compromised bone strength and increased susceptibility to fractures, with important health and socioeconomic consequences. Age remains a cardinal, independent determinant of fracture risk; hence, the prevalence of osteoporotic fractures is expected to rise as the proportion of older populations increases worldwide. The prevention of osteoporosis should begin early and continue all the way through life with measures that improve or maintain bone health including regular physical activity and a balanced diet, considering not only an adequate intake of calcium but also of other minerals, proteins, and food rich in antioxidants. Smoking and alcohol abuse should be avoided. In older persons, who are particularly at risk of fragility fractures, the prevention of falls and the maintenance of an adequate vitamin D status are essential. Assessment of fracture risk followed by proved effective nonpharmacological and pharmacological management is still low, even in patients who have sustained a fragility fracture. Nonpharmacologic strategies should always be implemented, but many patients also need pharmacologic intervention to achieve adequate fracture protection. It is clear today that although low bone mineral density (BMD) is an important determinant of bone fragility, it is not the only one, hence, drugs used in the treatment of osteoporosis must not only show to promote changes in BMD, but to reduce the incidence of fractures. Safety issues should be always considered in an individual basis. This article reviews the available nonpharmacologic and pharmacologic interventions -proved to be effective- that may be implemented to reduce the risk of osteoporotic fractures.